PEMBELAJARAN DENGAN PENDEKATAN OPEN ENDED SEBAGAI UPAYA PENINGKATAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS - Yuni Rhamayanti; Nurdalilah Nurdalilah (Universitas Muhammadiyah Tapanuli Selatan, 2018)
This research was conducted at the junior level students with the aim to improve the ability of the creative thinking of the students through the application of mathematical models of learning mathematics with the open ended approach. This type of research is Research Action class (Classroom Action Research), research done by the teacher in class of his own with a planned, systematic way to fix/improve the quality of practice learning in his class. As for the subject researches it is grade VII SMP Negeri Padangsidimpuan Year 7 Lesson 2017-2018, chosen was a Class VII-2 with the number of students is 22 people. Whereas the object of this research is the application of the model of learning mathematics with the open ended approach to increasing the ability of mathematical creative student berpkir is not good and needs to be fixed. Research instrument on this research will use the test engineering and non test. As for the test used was the ability of the creative thinking of the students in the form of mathematical problems such as shape description. While the test is the Non observation sheet and attitude. Based on the results and discussion in research then it can be drawn the following Conclusions 1) Increasing the ability of mathematical reasoning through the application of learning mathematics with the open ended approach on a grade VIII-2. As for the improvement of the ability of mathematical reasoning students acquired for 0.5 criteria are, and 2) based on the characteristics of the creative nature of the conformity with the students, obtained that most creative nature for compliance with students is the nature of curiosity.